Ichneumoniden aus Franken (Hymenoptera: Ichneumonidae). - Bauer, Rudolf (Contributions to Entomology = Beiträge zur Entomologie, 1958)
The author reports 915 species of Ichneumonidae from the environment of Nürnberg-Erlangen with a German summary containing additional notes on distribution and biology of these species.